Regulative Mechanism of Guanidinoacetic Acid on Skeletal Muscle Development and Its Application Prospects in Animal Husbandry: A Review - Yan, Zhaoming; Yan, Zhaoyue; Liu, Shuangli; Yin, Yunju; Yang, Tai; Chen, Qinghua (Frontiers in Nutrition, 2021)
Guanidinoacetic acid is the direct precursor of creatine and its phosphorylated derivative phosphocreatine in the body. It is a safe nutritional supplement that can be used to promote muscle growth and development. Improving the growth performance of livestock and poultry and meat quality is the eternal goal of the animal husbandry, and it is also the common demand of today's society and consumers. A large number of experimental studies have shown that guanidinoacetic acid could improve the growth performance of animals, promote muscle development and improve the health of animals. However, the mechanism of how it affects muscle development needs to be further elucidated. This article discusses the physical and chemical properties of guanidinoacetic acid and its synthesis pathway, explores its mechanism of how it promotes muscle development and growth, and also classifies and summarizes the impact of its application in animal husbandry, providing a scientific basis for this application. In addition, this article also proposes future directions for the development of this substance.